A Comparative Study of Anthropological Works of Subjectivism and Sadrian Belonging Existence - Simin Esfandiari (Pizhūhish/hā-yi Falsafī- Kalāmī, 2017)
Reflection on Mulla Sadra's philosophy helps us to find out that man has unlimited capacities which take on meaning in the world through realization. Since man as a limited being is existentially dependent upon infinite being, he tries to realize his existence and make a meaning for it. Therefore, we can understand the relationship between man and the world and his motion toward the Most High God, which is final end of all his motions, by taking into consideration man's belonging existence and the role of the world in making a meaning for his existence. However, "subjectivism" and confrontation between man and the world as one of its most important outcomes in western philosophy was developed as the result of Descartes's use of "self" as "subject" and "the world" as "object". The aim of present paper is to elaborate on the relationship between man and the world, given his mode of belonging existence in Sadrian philosophy contrasted with duality of man and the world which is an inevitable result of "subjectivism". Finally, it concludes that man's attachment and belonging to God in substantial motion and consequently his essential poverty is the factor that makes Sadrian man superior to the man in subjectivism and any kind of subjectivist thought.